Family Income, Parental Education and Chinese Preschoolers’ Cognitive School Readiness: Authoritative Parenting and Parental Involvement as Chain Mediators - Xia, Xiaoying (Frontiers in Psychology, 2022)
This study examined the associations of family income and parental education with Chinese preschool children’s cognitive school readiness and the sequential mediating role of parenting style (i.e., authoritative parenting) and parental involvement in these relations. A total of 307 5–6 years old kindergarten children from Shanghai, China and their parents participated in the study. Using structural equation modeling method, the results indicated that parental education was directly related to children’s cognitive school readiness, while no direct relationship was found for family income. The link of parents’ education with children’s cognitive school readiness was sequentially mediated by authoritative parenting and home-based parental involvement. Authoritative parenting and parental involvement at home can be targeted by government administrators to effectively improve children’s cognitive school readiness skills. The theoretical and practical implications were discussed.